Injury epidemiology in Australian male professional soccer - Lu, D.; McCall, A.; Jones, M.; Kovalchik, S.; Steinweg, J.; Gelis, L.; Duffield, R. (Journal of Science and Medicine in Sport, 2020)
Objectives: To describe the injury epidemiology of the Australian male professional soccer league (A-League) over 6 consecutive seasons. Design: Prospective observational cohort study. Methods: Match-loss injury data was collected from each A-League club (n = 10) for each competition match (n = 27/season) over 6 seasons (2012/13-2017/18). Injuries were collected weekly through a standardised protocol and were classified by setting, mechanism, severity, the type and location on the body. Generalised Linear Models were used to estimate the injury incidences (injury/round/season), whilst rate ratios were reported for total injuries and within abovementioned injury classifications. Results: Overall injury incidence was not significantly different ranging from 4.8 (95%CI:4.1-5.8) to 6.7 (95%CI:5.8-7.8) between seasons 2012/13 to 2017/18 (p > 0.05). Match injuries remained stable whilst training injuries decreased across the 6 seasons (exp(ß) 0.59[95%CI:0.36-1.0]; p = 0.04). Respectively, contact and non-contact injuries were not significantly different across the 6 seasons, although non-contact injuries were more common than contact injuries (p > 0.05). Mild severity injuries decreased (exp(ß) 0.64 [95%CI:0.4-0.9];p = 0.02), whilst moderate severity injuries increased (exp(ß) 1.7 [95%CI:1.0-2.8];p = 0.04) in season 2017/18 compared to 2012/13. The most common injuries were at thigh (23-36%), of which the majority were hamstring injuries (54%-65%) of muscle/tendon type (50-60% of total injuries/season). Injuries remained stable across the seasons by type and location (p > 0.05 and p > 0.05, respectively). Conclusions: Injury rates, mechanisms, locations and types have remained relatively stable over recent seasons of the A-League. Current Australian professional soccer league medical practices may have contributed to the stability of injury rates.